REQUIREMENT OF RESEARCH AS A LEARNING TOOL IN MEDICAL EDUCATION - LESS IS MORE. - Farooq, Saeed (Journal of Postgraduate Medical Institute, 2015)
The importance of research in providing evidence based solutions can't be overemphasized. Therefore almost all curricula both in under and postgraduate medical training have some components of training in research. This varies from teaching in statistics and epidemiology to writing a dissertation based on original data. In qualifications such as M Phil or PhD, the requirement of original research work is understandable but it is of questionable value in clinical qualifications such as FCPS. To the best of authors' knowledge the comparable qualifications like MRCP or FRCS do not require original research work. The requirement of dissertation based on original research work may be desirable for promoting research in the country but its value as a tool to enhance training in research is questionable. It is important that we are clear about the learning objectives, assessment methods and how this will contribute to the development of student when we are using any learning tool. As far as I am aware these have not been defined clearly for a dissertation or similar requirement in a most medical qualification. It is time to examine the value of dissertation or similar tools in medical education.